Effectiveness of a Short-Term Treatment of Oxygen-Ozone Therapy into Healing in a Posttraumatic Wound. (22nd August 2016) - Degli Agosti, Irene; Ginelli, Elena; Mazzacane, Bruno; Peroni, Gabriella; Bianco, Sandra; Guerriero, Fabio; Ricevuti, Giovanni; Perna, Simone; Rondanelli, Mariangela
Abstract : Introduction . A number of studies suggest that oxygen-ozone therapy may have a role in the treatment of chronic, nonhealing, or ischemic wounds for its disinfectant and antibacterial properties. Nonhealing wounds are a significant cause of morbidity. Here we present a case of subcutaneous oxygen-ozone therapy used to treat a nonhealing postoperative wound in a young man during a period of 5 weeks. Case Presentation . A 46-year-old man had a motorcycle accident and underwent amputation of the right tibia and fibula. At the discharge he came to our attention to start rehabilitation treatment. At that time the wound was ulcerated but it was afebrile with no signs of inflammation and negativity to blood tests. At 2 months from the trauma despite appropriate treatment and dressing, the wound was slowly improving and the patient complained of pain. For this reason in addition to standard dressing he underwent oxygen-ozone therapy. After 5 weeks of treatment the wound had healed. Conclusion . In patients with nonhealing wounds, oxygen-ozone therapy could be helpful in speeding the healing and reducing the pain thanks to its disinfectant property and by the increase of endogenous oxygen free radicals' scavenging properties. Compared to standard dressing and other treatments reported in the literature it showed a shorter time of action.